Prospective Evaluation of Outpatient Flexible Sigmoidoscopy in Patients With Deep Infiltrating Endometriosis. Issue 6 (December 2020) - Celentano, Valerio; Di Donato, Nadine; Buccomino, Giusy E.; Candy, Katie; Solomon, Lemke; Ihezue, Chukwumobi; Berry, Janet; Tsepov, Denis
Abstract : Introduction: To study patients' acceptability of an outpatient flexible sigmoidoscopy (FS) protocol and to assess the diagnostic value of endoscopic assessment in patients with deep endometriosis (DE). Methods: All patients with DE and suspected bowel involvement diagnosed were reviewed in the colorectal outpatient clinic before elective surgery following multidisciplinary team meeting discussion. Patients were consented for having the FS performed at the same time of the clinical consultation. Primary outcome was diagnostic value of the FS. Results: Sixty patients were included. Fifty-eight (96.7%) patients consented for the outpatient FS, demonstrating a high rate of patients' acceptability. The sigmoidoscopy demonstrated no abnormalities in 48 patients (82.7%), diverticulosis in 5 patients (8.6%), polyps in 2 patients (3.4%) and mucosal endometriosis in 1 patient only (1.7%). Conclusions: Outpatient FS during the preoperative consultation with the colorectal surgeon is feasible in patients with DE affecting the bowel with a high rate of patients' acceptability but limited additional diagnostic value.